2021
DOI: 10.32604/cmc.2021.018593
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sentiment Analysis Using Teaching-Learning Based Algorithm

Abstract: Feature selection and sentiment analysis are two common studies that are currently being conducted; consistent with the advancements in computing and growing the use of social media. High dimensional or large feature sets is a key issue in sentiment analysis as it can decrease the accuracy of sentiment classification and make it difficult to obtain the optimal subset of the features. Furthermore, most reviews from social media carry a lot of noise and irrelevant information. Therefore, this study proposes a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The method fulfilled its objective of increasing performance, reducing the computational cost, increasing accuracy, removing irrelevant data, and helping faster model learning. Muhammad et al [ 167 ] presented a novel text feature selection technique that used an amalgamation of rough set theory (RST) and TLBO known as RSTLBO. They developed four frameworks in the RSTLBO: the acquisition of standard datasets, dataset pre-processing,utilizing the RSTLBO method; selected feature set used by employing the SVM technique.…”
Section: Metaheuristic Algorithms For Multiclass Feature Selectionmentioning
confidence: 99%
“…The method fulfilled its objective of increasing performance, reducing the computational cost, increasing accuracy, removing irrelevant data, and helping faster model learning. Muhammad et al [ 167 ] presented a novel text feature selection technique that used an amalgamation of rough set theory (RST) and TLBO known as RSTLBO. They developed four frameworks in the RSTLBO: the acquisition of standard datasets, dataset pre-processing,utilizing the RSTLBO method; selected feature set used by employing the SVM technique.…”
Section: Metaheuristic Algorithms For Multiclass Feature Selectionmentioning
confidence: 99%
“…An approach for analyzing sentiment is used for datasets gathered from Arabic social media, in which a corpus is manually built, as detailed in [10]. The outcomes of this research are reported in [11]. Several ML techniques are executed on the training and testing datasets to ascertain whether or not the suggested approach produces accurate results.…”
Section: Related Workmentioning
confidence: 99%
“…A set of machine learning algorithms are applied to the training and testing datasets to identify the accuracy of the proposed approach. As presented in [8], a sentiment analysis mechanism is proposed for processing sentiments from learning and teaching datasets. A feature selection is applied to the processed data by creating four models and a sentiment classification using a support vector machine (SVM) algorithm is implemented to provide the accuracy of the models.…”
Section: Supervised Sentiment Analysismentioning
confidence: 99%
“…Language Polarity /Weight Mechanism [7] Apply classification algorithms on a corpus approach for analyzing sentiments and terms. Arabic 3-Weight Supervised [8] Classify learning datasets using SVM algorithm. English 3-Weight Supervised [9] Classifying tweets using Naïve Bayes.…”
Section: No Objectivementioning
confidence: 99%